Guidelines for Evaluating Pancak Silat Referees in Thailand - Jaisamut, Serbsakul; Praditsarn, Somphob; Chandanouvong, Sonephet; Damteh, Yusob (Journal of Education Rajabhat Maha Sarakham University, 2025)
The purpose of this research was to develop guidelines for evaluating Pancak Silat referees in Thailand. The research method included: 1) document synthesis along with in-depth interviews using semi-structured interviews with 9 experts until data saturation is reached to create guidelines for evaluating referees; 2) once the guidelines for evaluating referees were developed, the consistency was verified using Modified Delphi technique with 17 experts, employed a closed-ended questionnaire; and 3) conducting focus group discussion with 8 stakeholders to confirm the applicability of the guidelines for evaluating referees. The statistics were Index of Item Objective Congruence (IOC), median, and interquartile range. The results of the research revealed that the guidelines for evaluating Pancak Silat referees in Thailand were appropriate and feasible for implementation. There were comprising of 5 components and 31 indicators as follows: 1) 7 indicators in Knowledge, 2) 12 Indicators in Skills, 3) 4 Indicators in Work Performance, 4) 4 indicator in Attitude, and 5) 4 indicators in Career Advancement. Each indicator and evaluation criterion was set with a passing threshold of 4 points out of a total of 5 points. The result from the focus group discussion with stakeholders confirmed and suggested that these evaluation guidelines are suitable and feasible for evaluating Pancak Silat referees.